RESPONSE ASSESSMENT AND OUTCOMES IN PEDIATRIC B CELL NON-HODGKIN LYMPHOMA: OUR EXPERIENCE AT SHAUKAT KHANUM MEMORIAL CANCER HOSPITAL AND RESEARCH CENTRE - Rehman, Palwasha; Wali, Rabia Muhammad (Pakistan Armed Forces Medical Journal, 2020)
Objective: To determine the relation of response assessment and outcome of B cell non-Hodgkinlymphoma so we can minimize utilization of our resources. Study Design: Retrospective observational study. Place and Duration of Study: Pediatric Oncology Department, Shaukat khanum Memorial Cancer Hospital and Research Centre, from Jan 2013 to Dec 2016. Methodology: Patients from the age of 1 till 18 years presented at Shaukat khanum hospital were included in the study. Patients were staged as per St. Jude staging system and response assessment done as per French-American British (FAB) Lymphome Malins De Burkitt (LMB) protocol. Results: Total 247 patients diagnosed with B cell Non-Hodgkin Lymphoma were included. When the interim scans were compared with the end of treatment assessment, 139 (82.2%) patients (n=169) had achieved complete morphological remission on the re-evaluation scans, 138 patients (86.2%) among them were in remission at end of treatment where as 01 patient had relapse disease. The interim disease re-evaluation scan is predictive of end of treatment response with sensitivity of 86.8%, specificity of 88.9% (p-value <0.005) Conclusion: The patients who achieved rapid response on re-assessment scans have good outcomes. We recommend that in future patient’s with complete response on interim scans to be followed with ultrasonography or clinical examination to minimize expenditures and radiation exposure.